Mechanical properties of flexure and shear of commercially available timber beams in the Philippines - De Guzman, Earl Marvin B.; Go, Michael Stephen C.; Tengki, Katrina C.; Oreta, Andres Winston C.
Commercially available wood used as structural members are commonly referred to as "good lumber." Good lumber consists mostly of imported wood, and those of lesser known or unknown local species. With the wood species not clearly specified, there is a need to determine the mechanical properties of good lumber. Standard laboratory tests were conducted to determine the range of values of good lumber properties including moisture content, specific gravity, modulus of elasticity and the bending and shear strength of timber beams. The mechanical properties of good lumber were obtained through a series of laboratory tests that simulated the conditions for the loading schemes specified in the ASTM manual on beams of nominal cross section 2" x 4". With the information on the variation of strengths of good lumber, structural designers can be guided on appropriate allowable stresses in designing structural members such as purlins and joists made of commercially available wood with unknown species.
Keywords: Timber -- Shear (Mechanics) -- Philippines; Timber -- Flexure -- Philippines; Philippine lumber